Internationalising the curriculum: building intercultural understandings through music - Joseph, Dawn (Journal of University Teaching and Learning Practice, 2012)
This article reports of the power (influence) of music to develop intercultural understandings to better internationalise the curriculum. It argues that through internationalisation, we learn more about other people’s cultures hence, by providing an international/intercultural dimension into the teaching unit of ‘Discovering Music A’, tertiary students at Deakin University have opportunities to experience, investigate and participate in a different music and culture. Using the metaphor of the ‘talking drum’, this article reports through anecdotal notes, observations, journaling and student evaluation, how a different music, like that of Africa, communicates and promotes intercultural dialogue in a social and learning environment. The 2011 cohort included both international and local students from the Faculty of Arts and Education, Health and Business and Law, opening up a broad range of international dialogue in which all students in the cohort had a voice for expressing themselves about another culture and its music. I contend that the inclusion of a new and different music in the Bachelor of Education (Primary) curriculum and as an elective unit across all faculties provides a pathway for intercultural dialogue and understanding. As tertiary educators by internationalising the curriculum and through the process of reflection, observation and student feedback, we are able to make meaning around our practice and adapt our practice. I argue that units like Discovering Music A are an effective and useful dais to address cultural diversity and build intercultural relations and understandings in our tertiary courses.